Sosialisasi Kebersihan Lingkungan dari Sampah Plastik pada Daerah Pesisir di Kelurahan Sasa Kota Ternate - Arif, Nurfadhilah; Nurjannah, Siti (Jurnal Pengabdian Masyarakat Hutan, 2024)
Ocean waste is currently a global problem in the environment, especially plastic waste. It can harm living things (such as human, coastal fauna and flora) and marine transportation systems. This activity aims to socialize and assist coastal resident in Sasa Village with giving knowledge and awaken public awareness about the dangers of plastic waste in the community, Beside that, the team also inviting the community to participate in cleaning coastal area in Sasa Village. To achieve this aims, activities have been carried out: socialization and beach clean-up actions. The results obtained from this activities are as follows: (1) The socialization activity went well and received a positive response from residents in Sasa Village (2) The beach clean-up activity was carried out together with several students and local residents. The results of the waste collection collected were 20 bags of rubbish.